Analysis of Sharia Tourism Development on Revenue and Financial Statements Before and After Sharia Tourism Development - Nasution, Emmi Suryani; Syamsidar, Syamsidar; Riski, Fajar (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to determine the growth in income earned by traders and community members in the Ulee Lheu Beach tourism area. The research approach employed was descriptive qualitative research, which aimed to accurately depict the impact of tourism development on community income in Meuraxa District, Banda Aceh City. The study's sample size was 78 respondents, and the data were obtained by questionnaire and processed using descriptive qualitative methodologies. The study's findings show that while the income of business actors at the Ulee Lheu Beach tourist attraction has increased as tourism has grown, employment remains relatively low.